KONSEP DAKWAH DALAM PERSPEKTIF ABDURRAHMAN WAHID (GUS DUR) (STUDI ANALISIS METODE DAKWAH) - Nurhidayatullah Tawiluddin (Jurnal Dakwah Tabligh, 2020)
This study describes the da'wah concept of Abdurrahman Wahid in the study of da'wah analysis methods, which aims 1) to describe the concept of 'Abdurrahman Wahid's da'wah, and 2) describe the Abdurrahman Wahid da'wah method. This research is a type of qualitative research through library research, using a normative approach, da’wah, and historical. The data collection method in this study was through collecting documents. The instrument in this study was the researcher himself (human instrument). The results of this study indicate, 1) Abdurrahman Wahid is a figure dai who has the character of pluralism with a moderate concept of da'wah. This is supported by the characteristics of preaching that upholds the principle of justice (al-‘adalah), the principle of balance (tawaz}un), and the principle of tolerance (tasa>muh). And Abdurrahman Wahid is able to do two approaches to preaching at the same time, namely the structural da'wah approach and the cultural da'wah approach which causes his da'wah to be accepted by various groups. 2) The spirit of Abdurrahman Wahid's da'wah method is contained in Q.S.an-Nah}l/16:125 which includes three forms of the application of the da'wah method, namely Da'wah bi al-lisa>n as an effort in guiding people, da'wah bi al-h}a>l as an effort to raise awareness and develop the ability of the people, as well as the da’wah bi al-qalam as an effort to transform science. Abdurrahman Wahid's da'wah method is a method that is progressive because Abdurrahman Wahid strives for a change that occurs among people who are advanced, improved and sustainable both in quantity and quality. The implications of this research are 1) Research on the concept of Abdurrahman Wahid's da'wah is an attempt to explore, discover, and reconstruct his moderate preaching thoughts, with the object of preaching being a pluralistic Indonesian society. Thus, the objectives of the reconstruction results can be used as a model for the implementation and development of da'wah. 2) The concept of moderate progressive da'wah is one alternative da'wah concept suitable for development in Indonesia. The results of this study add and complement the repertoire and literature in the field of da'wah. Therefore, similar research can be carried out on other da'wah figures both at the local and national level.